Achieving charge density wave transition at room temperature in 2D non-layered transition metal dichalcogenide CoS. Issue 38 (1st September 2022) - He, Xu; Hong, Wenting; Jian, Chuanyong; Sun, Fapeng; Cai, Qian; Liu, Wei
Abstract : The observation of room-temperature charge density wave phases in the non-layered two-dimensional material CoS is reported. Abstract : The charge density wave (CDW) state has drawn tremendous interest due to the periodically modulated charge distribution that distorts a metallic lattice into an insulating state. However, the cryogenic temperatures needed to access the commensurate CDW state limit the development of CDW-based electronic devices. Herein, for the first time, we report a room-temperature CDW phase non-layered two-dimensional (2D) material, CoS. The emergence of (2 × 2) ordering observed via selected area electron diffraction confirmed the CDW state. The transition temperature ( T CDW ) of the CDW, measured via temperature-dependent resistance measurements, is ∼296 K. The observation of the room-temperature CDW transition in non-layered CoS at ambient pressure provides an engineering approach as needed in applications, which not only opens up new property investigations on non-layered 2D materials but also promotes the practical development of CDW-related technology and devices.